Effect of Moringa Oleifera Leaf Nanoparticles on IL-10 in Vivo Model of Oral Cavity Malignancy - Asmaningdiah, Mariana; Andriyani, Alfia (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Interleukin-10 (IL-10) which is secreted by Th 2 cells. Interleukin- 10 is an anti-inflammatory cytokine that plays an important role in the regulation of the host immune response by inhibiting the release of pro-inflammatory mediators. Moringa leaf nanoparticles (Moringa oleifera) are products that contain various bioactive mediators that can play a role in inflammation. The aim of this study was to determine the effect of administering Moringa leaf extract nanoparticles on IL-10 levels in oral cavity cells undergoing malignant transformation. Eighteen male Wistar rats (R. novergicus) were used as animal models that underwent benzo(a)pyrene induced malignant transformation in the oral cavity. Moringa leaf extract nanoparticles with concentrations of 0.250 mg/mL, and 0.500 mg/ were given to the treatment group for 14 days. The results of IL-10 levels were evaluated using the ELISA method. Data analysis using the Kruskall-Wallis test was carried out to analyze differences between groups. Aplication Moringa oleifera leaf nanoparticles with concentrations of 0.250 mg/mL, and 0.500 mg/mL were able to reduce levels of IL-10 in oral cells undergoing malignant transformation. The results of this study showed that the p-value = 0.726 (> 0.05) which means that there was no effect of the application of moringa leaf extract nanoparticles in a mouse model with malignant transformation of oral cells on reducing IL-10 levels.